1999
DOI: 10.1093/ndt/14.suppl_6.10
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare systems and end-stage renal disease (ESRD) therapies--an international review: access to ESRD treatments

Abstract: Assessment of healthcare technology and economics can be used to assess the access to healthcare, its quality and efficacy as well as its cost and cost efficiency. This report addresses these issues for the provision of care for end-stage renal disease (ESRD) patients. An international comparison of access to ESRD treatment modalities was made with reference to the healthcare provider structure in a range of industrial countries. The countries were grouped into 'public' (Beveridge model), 'mixed' (Bismarck mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 0 publications
2
46
0
1
Order By: Relevance
“…25 Previous studies showed a positive association between RRT incidence and the share of private for-profit HD facilities. 26,27 Our results are in line with them and add that the higher incidence may be caused in part by applying higher target eGFRs at RRT initiation. With this international survey including 11 European countries, we examined a wide range of current opinions of nephrologists' on their decision for when to start RRT.…”
Section: Most Frequently Mentioned Reasons As Basis For Opinion (% Ofsupporting
confidence: 88%
“…25 Previous studies showed a positive association between RRT incidence and the share of private for-profit HD facilities. 26,27 Our results are in line with them and add that the higher incidence may be caused in part by applying higher target eGFRs at RRT initiation. With this international survey including 11 European countries, we examined a wide range of current opinions of nephrologists' on their decision for when to start RRT.…”
Section: Most Frequently Mentioned Reasons As Basis For Opinion (% Ofsupporting
confidence: 88%
“…3 For example, countries with private dialysis providers generally use PD for a smaller proportion of dialysis patients than countries in which public providers dominate. [25][26][27] The proliferation of HD units in some countries has increased the availability of HD, creating an incentive to use that capacity rather than home dialysis modalities. 23,28 Some have raised concerns that nephrology training programs are deficient in PD and do not adequately prepare young nephrologists to provide care for PD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons of our results with those from other authors (21)(22)(23)(24)(25)(26)(27) are difficult because of differences in the methods of data collection and evaluation, resources analyzed, period of investigation, and cost of living in various locales. However, our study more comprehensibly evaluated the principal DMC of the medical care process.…”
Section: Discussionmentioning
confidence: 59%